ANALYSIS OF STUDENTS SCIENCE PROCESS SKILLS ON DIGESTIVE SYSTEM LEARNING USING THE 7E LEARNING CYCLE MODEL - Bunga Indah Aprilyani Silitonga; Abdul Rasyid Fakhrun Gani; Melva Silitonga (Jurnal Pelita Pendidikan, 2021)
This study aimed to obtain data on students' science process skills on the digestive system material for class XI MIPA. This research type is research pre-experimental with one case study. The population in this study were students of class XI MIPA with a sample of 35 students using random sampling techniques. The learning stages in this phase include Elicit, Engage, Explore, Explain, Elaborate, Evaluate and Extend. The data were analyzed with the average value and then analyzed using Anova. The results of this study indicate that the science process skills in nine aspects are classified as very high for observing and communicating (each with a value of 95 and 84.64), that are classified as high are grouping (67.85), predicting (68.57), asking questions (62.85), proposing hypotheses (74.64), and planning research (80.35). Science process skills classified as moderate are aspects of data interpretation (52.85), and those classified as low apply concepts (38.57). Based on the Anova test, the value of science process skills on nine aspects was significantly different at the significance level α <0.05. The conclusion is that students' science process skills are classified as high and have differences in every aspect.